การวิเคราะห์ชีวิตการทำงานของครูในยุคดิจิทัล - สิริวัฒน์โสภณ จุฑามาศ; ศรีเคลือบ กนิษฐ์; ว่องวาณิช สุวิมล (An Online Journal of Education, 2018)
The Objectives of this research were to 1) analysis compare teacher worklife in digital age 2) to compare teacher worklife in digital age between group with different experience and school sizes. The subjects consisted of 539 teachers who work in schools under the Office of the Basic Education Commission. The data were collected by a rating scale of 5 levels questionnaires. The IOC results showed that all item fell in the acceptable IOC range of 0.86 to 1.0. Conducted reliability analyses produced a Cronbach alpha reliability coefficient of 0.962 for the whole scale. The structural validity of the scale fitted well with empirical data. The descriptive statistics, and two-way MANOVA were used to analyze data. Research findings are summarized as follows: 1) Teacher had high levels of teacher worklife in digital age (M = 3.71, SD = 0.64), the working behaviour (M = 3.59, SD = 0.71), the working feeling (M = 3.83, SD = 0.68), but a moderate level of the working behaviour of teachers who have experience less than 1 year (M = 3.49, SD = 0.66) and teachers who work small-sized school. (M = 3.48, SD = 0.75) 2) There are no interaction between experience and school sizes to the working behaviour and the working feeling at the .05 level of significance. The working behaviour and the working feeling of teacher that work in extra-large sized school were higher than medium-sized school and small-sized school respectively.